An experimental study of an air-blast atomiser - Bryan, R. H. (Cranfield University, 1967)
Visual observations and an optical method of measuring the mean droplet size in sprays have been used to assess the performance of a prototype airblast atomiser, particularly at the low fuel and air flow conditions corresponding to engine cranking. The results obtained from this and a shroud version of the same basic atomiser have enabled design modifications to be made which have resulted in a marked improvement in performance, both in terms of the spraying characteristics of the atomiser at low fuel and air flows, and in terms of the measured droplet size produced. The latter for the final design was very close to that predicted by Wiggs for airblast atomisers operating at the test conditions employed. An apparatus has also been designed to enable tests on the atomisation quality of airblast atomisers to be carried out at pressures up to 250 p.s.i.,, using the same optical technique to make mean droplet size measurements.